The effect of grain boundary on Na ion transport in polycrystalline solid-state electrolyte cubic Na3PS4 - Yixuan Wang; Gengwei Li; Kun Shen; Enke Tian (Materials Research Express, 2021)
In the polycrystalline solid-state electrolytes (SSEs), ionic transport is directly linked to the properties of all solid-state batteries. Grain boundaries (GBs), as essential defects in SSE, were found to play a significant role in the overall kinetics of Na ion transport, while the mechanism is not well understood due to the complex role of GBs. In this study, the first principles and phase field calculations are combined to explore the diffusion path and the interaction between point defects and grain boundaries in cubic Na _3 PS _4 at different scales. The effects of point defects segregation on the overall kinetics of ionic transport were discussed in detail. By comparing the energy barriers required for ion transition along GBs and across GBs, the effect of the grain boundary on ionic diffusion can be influenced by local atomic coordination. This study could help improve the fundamental understanding of ionic transport in polycrystalline solid-state electrolytes, and provide guidance for designing new solid-state electrolytes with excellent ionic conductivity.